Country Attractiveness: Analysis of the Main Factors - A. G. Avetisyan (Финансы: теория и практика, 2020)
Attracting investment is a relevant issue for any economy. The aim of the research is to study the factors affecting the inflow of foreign direct investment (FDI) by the example of countries leading in attracting FDI and countries of the Eurasian Economic Union (EAEU). The author uses both qualitative and quantitative methods to analyze research data of other authors, reports of international organizations and the World Bank database. The author did econometric calculations using the application package Stata 14. A linear regression model using the least-squares method was built. The author selected several factors that presumably affect FDI inflows to the EAEU countries. The calculations were based on the combined panel data analysis model used in the BRICS and MINT countries, which allowed the author to calculate the degree of influence and significance of a number of variables of FDI inflows. The study shows that political stability is more important than the inflation rate, the volume of foreign trade and final consumption expenditure. The author concluded that poor institutional development hinders investment. In particular, the negative institutional factors are non-transparent regulation policy, the dominance of public property and the lack of proper investment protection system, low degree of rule of law and limitation of economic rights. Further study of issues related to attracting FDI should consider the trends of mass digitization since the introduction and implementation of digital technology are becoming an integral part of the competitiveness of the modern economy.